Effect of specialist palliative care services on quality of life in adults with advanced incurable illness in hospital, hospice, or community settings: systematic review and meta-analysis. (4th July 2017) - Gaertner, Jan; Siemens, Waldemar; Meerpohl, Joerg J; Antes, Gerd; Meffert, Cornelia; Xander, Carola; Stock, Stephanie; Mueller, Dirk; Schwarzer, Guido; Becker, Gerhild
Abstract : Objective To assess the effect of specialist palliative care on quality of life and additional outcomes relevant to patients in those with advanced illness. Design Systematic review with meta-analysis. Data sources Medline, Embase, Cochrane Central Register of Controlled Trials, PsycINFO, and trial registers searched up to July 2016. Eligibility criteria for selecting studies Randomised controlled trials with adult inpatients or outpatients treated in hospital, hospice, or community settings with any advanced illness. Minimum requirements for specialist palliative care included the multiprofessional team approach. Two reviewers independently screened and extracted data, assessed the risk of bias (Cochrane risk of bias tool), and evaluated the quality of evidence (GRADE tool). Data synthesis Primary outcome was quality of life with Hedges' g as standardised mean difference (SMD) and random effects model in meta-analysis. In addition, the pooled SMDs of the analyses of quality of life were re-expressed on the global health/QoL scale (item 29 and 30, respectively) of the European Organization for Research and Treatment of Cancer QLQ-C30 (0-100, high values=good quality of life, minimal clinically important difference 8.1). Results Of 3967 publications, 12 were included (10 randomised controlled trials with 2454 patients randomised, of whom 72% (n=1766) had cancer). In no trial was integration of specialist palliative care triggered according to patients' needs as identified by screening. Overall, there was a small effect in favour of specialist palliative care (SMD 0.16, 95% confidence interval 0.01 to 0.31; QLQ-C30 global health/QoL 4.1, 0.3 to 8.2; n=1218, six trials). Sensitivity analysis showed an SMD of 0.57 (−0.02 to 1.15; global health/QoL 14.6, −0.5 to 29.4; n=1385, seven trials). The effect was marginally larger for patients with cancer (0.20, 0.01 to 0.38; global health/QoL 5.1, 0.3 to 9.7; n=828, five trials) and especially for those who received specialist palliative care early (0.33, 0.05 to 0.61, global health/QoL 8.5, 1.3 to 15.6; n=388, two trials). The results for pain and other secondary outcomes were inconclusive. Some methodological problems (such as lack of blinding) reduced the strength of the evidence. Conclusions Specialist palliative care was associated with a small effect on QoL and might have most pronounced effects for patients with cancer who received such care early. It could be most effective if it is provided early and if it identifies though screening those patients with unmet needs. Systematic review registration PROSPERO CRD42015020674.